AN INVESTIGATION INTO THE RELATIONSHIP BETWEEN ENDOMETRIOSIS AND THE OUTCOMES EXPERIENCED BY INFERTILE PATIENTS - Dhankhar, Sunita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Introduction: Females of reproductive age have a 6–10% prevalence of endometriosis. About 25–35% of women who are infertile may have endometriosis. Treatment options for infertile patients vary according to the disease's stage. It begins with an ovulation-inducing medication a8ch ogresses to sophisticated ART. The purpose of the current research was to appraise the outcomes of surgical intervention on endometriosis subjects who are otherwise infertile. Materials and methods: The research was undertaken in selected government hospitals at Delhi. This study included 150 patients in all, ranging in age from 20 to 40. Every demographic factor, clinical and sonographic result, and hormonal evaluation was completed. Following that, staging was completed using ultrasonographic results and a clinical pelvic evaluation. For laparoscopic surgery, patients with ovarian endometriomas larger than 4 cm were chosen. Patients who did not have an ovarian endometrioma or whose endometrioma measured less than 4 cm were selected for ovulation induction, whether or not they had previously had GnRH agonist therapy. Results: The patients' mean age was 29.64 years & 70.52% had pry. infertility. Dysmenorrhea (76.24%) followed by Menorrhagia (54.61%) and chronic pelvic (40.51%) were the most important clinical symptoms. Decreased serum AMH was linked to bilateral endometrioma. The primary treatment was laparoscopic surgery. The remaining patients received conservative care. IUI and controlled ovarian stimulation were employed after ovulation-inducing drugs like letrozole and GnRH agonists were used to boost fertility. In 25 patients (33.33%), IVF was recommended for fertility management. In conclusion, endometriosis causes a reduced response to ovarian stimulation in addition to being linked to a decreased ovarian reserve. Therefore, obtaining effective reproductive treatment for this patient population is quite difficult.